2018
DOI: 10.1080/1028415x.2018.1427659
|View full text |Cite
|
Sign up to set email alerts
|

Oral solution of fructose promotes SREBP-1c high-expression in the hypothalamus of Wistar rats

Abstract: Dietary fructose can change important lipogenic and inflammatory factors in the hypothalamus of rats and it leads to regulation of transcription factors before changes in body mass are evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The results show that 30% fructose solution causes a significant increase in BW. It was reported that 20% fructose solution did not cause change in both BW and biochemical parameters (2). In this study, as well as BW, liver weights were similar in F15 and F60.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The results show that 30% fructose solution causes a significant increase in BW. It was reported that 20% fructose solution did not cause change in both BW and biochemical parameters (2). In this study, as well as BW, liver weights were similar in F15 and F60.…”
Section: Discussionsupporting
confidence: 63%
“…In a study, SREBP-1c and ACACA gene expression increased in the hypothalamus with 20% fructose consumption, while FAS was downregulated (2). In addition, it was reported that food intake was suppressed through FAS inhibitors in the hypothalamus, preventing body weight gain (2). With this study, lipogenic genes activity has been determined that strongly changed with the fructose consumption in liver.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…It was thought that NRF-2 acts with COX-2 gene expression level up to a certain concentration of consumed fructose in drinking water, but this effect disappears when the concentration of consumed fructose increases. It was stated that the reaction to fructose in metabolism varies according to the amount and duration of exposure (1,4,6). There was no significant relationship between MDA level and COX-2, NRF-2 gene expression other than the 2 above mentioned.…”
Section: Discussionmentioning
confidence: 99%